A comparative study of three onshore wind turbine foundation solutions. (February 2018) - Mohamed, Wael; Austrell, Per-Erik
Abstract: This work focuses on the geotechnical behaviour of three foundation solutions for windmills. The first design is a traditional flat raft, the second is a deep flat raft, and the third is a conical raft. A comparative study between the traditional and the new solutions is performed. A conical raft is used to improve the resistance of the soil–structure interface. It is shown that a conical raft gives a significant decrease of tilting compared to a flat circular raft. The use of a conical raft can thus decrease the dimensions of the foundation which may lead to potential cost reductions.